Students' Mathematical Problem Solving Ability in Linear System with Two Variable - Putri, Dela Rahayu; Nasir, Fuad; Maharani, Anggita (FKIP Universitas Lampung, 2022)
Considering that mathematics has an important role in learning and in everyday life, the process of learning mathematics that hones the problem solving skills of people who play a role in solving the problem, usually mathematics based on this problem uses questions that contain elements of contextual problems that intersect with students' daily lives. . The aim is to describe students' mathematical problem solving abilities on the material of a two-variable system of linear equations. Class VIII students are the subjects of this research. The indicators according to Polya are (1) Understanding the Problem, (2) Developing a Plan, (3) Implementing a Solution Plan, (4) and Reviewing the Overall Answer. The result of this research is to have an average in the medium category. In the process of completing all Polya indicators, students were able to meet all indicators, but students who had moderate mathematical problem solving abilities were only able to fulfill the indicators of planning and reviewing overall answers, while students with low mathematical problem solving abilities could not fulfill all existing indicators.Keywords: mathematical problem solving ability, system of two variable linear equations.DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1839-1849